Legislative oversight and structural violence in the Lagos State Health Scheme: A study of Alimosho Local Government Area - Dele-Dada, Moyosoluwa; Gberevbie, Daniel; Owolabi, Fadeke (Research Journal in Advanced Humanities, 2024)
Structural violence imposes constraints on achieving equitable, affordable, accessible, and high-quality public services, encompassing healthcare. Despite establishing the LSHS, aimed at providing healthcare irrespective of economic status, residents continue to experience deprivation, restricted access, and substandard healthcare services. Doubts arise regarding the efficacy of legislative oversight in mitigating structural violence. This study explores this issue by employing a comprehensive methodology involving primary and secondary data collection through literature reviews, questionnaires, and interviews. The analysis reveals that the prevalence of structural violence within the LSHS cannot be exclusively attributed to deficiencies in the oversight responsibilities of the Lagos State House of Assembly. Lingering disparities, limited accessibility, unaffordability, and inadequate healthcare quality persist. Contributing factors encompass inadequate funding mechanisms, and deficiencies in communication, among others. Challenges such as executive interference, corruption, and the absence of a robust legislative framework impede the effectiveness of oversight.